Analysis of the Satisfaction Level of the Dendang Laut Community towards the Quality of Public Service of the Laut Dendang Village Office - Muhammad Arif Hidayah; Sri Sudiarti (Journal of Indonesian Management, 2022)
This study was conducted to determine whether the service quality of the Laut Dendang Village office has an effect on the satisfaction level of the Laut Dendang Village community. This type of research is a quantitative descriptive analysis researcher, where the object of research is the village office of Laut Dendang, the population is the surrounding community and the sample is people who already have ID cards, the data collection technique is through a questionnaire to the respondents. Data analysis in this study used correlation coefficient analysis, reliability test, validity test, classical assumption test, regression analysis, coefficient of determination analysis, hypothesis testing and also hypothesis testing using SPSS application. The results showed that the level of service quality had a positive effect on the satisfaction of the people of Laut Dendang Village.